Penerapan Penerapan IPTEK Guna Meningkatkan Produktivitas Bakmi Pakcoy Melalui Pelatihan Teknik Pengemasan Mie Dengan Metode Vakum Press : Penerapan IPTEK Guna Meningkatkan Produktivitas Bakmi Pakcoy Melalui Pelatihan Teknik Pengemasan Mie Dengan Metode Vakum Press - Visca, Rinette; Nuriaini Dewi, Mubarokah; Elvistia F, Flora; Agusta, Harini; Khodijah N, Siti; Salahhudin, Salahhudin; Rifai, Muhammad; Artana, I Nyoman (Universitas Jayabaya, 2023)
Bok choy noodles are made from bok choy vegetables produced by residents of the Pabuaran Asri Housing Complex, Pabuaran Mekar Village, Cibinong District. In terms of production aspects, Bok choy noodles experiences problems in packaging noodle products because the consumer's location is quite far. One solution offered is to package the noodles in vacuum packaging using a vacuum press. This service activity was designed by the Faculty of Technology, Jayabaya University together with students with the theme of providing knowledge to the public about food packaging technology. The community group targeted was the Women's Farmers Group (KWT) RW 08. The aim of the community development activity is KWT members have knowledge of noodle packaging techniques and skills in using a vacuum press tool. The method used was counseling and training on tool use with a total of 14 participants. From the survey results, it was found that there was an increase in participants' knowledge and insight regarding noodle packaging technology.